Fertility-preserving management of an inflammatory myofibroblastic tumor: A case report and review of the literature - Geneviève Horwood; Aurelia Busca; Sukhbir Singh (Elsevier, 2023)
Molecular diagnostics have broadened the categorization of mesenchymal tumors of the uterus. Knowledge of the increasing heterogeneity of uterine neoplasms is paramount for the gynecologist as the management and prognosis of these neoplasms differ from those of typical leiomyomas.In this case, a 26-year-old nulligravid patient underwent hysteroscopic management for an enlarging submucosal neoplasm of the uterus. She was found to have an inflammatory myofibroblastic tumor (IMT) after ALK (anaplastic lymphoma kinase) immunostaining. Upon review of pathologic characteristics, she was treated expectantly with repeat hysteroscopy 12 months later. Ongoing conservative management will entail serial pelvic imaging.IMTs should be considered in the differential diagnosis of fibroids presenting in young women. Fertility-preserving management in select patients is appropriate after patient counselling.